2015
DOI: 10.3390/computers4030251
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Elbow Angle for Extracting sEMG Signals During Fatiguing Dynamic Contraction

Abstract: Surface electromyographic (sEMG) activity of the biceps muscle was recorded from 13 subjects. Data was recorded while subjects performed dynamic contraction until fatigue and the signals were segmented into two parts (Non-Fatigue and Fatigue). An evolutionary algorithm was used to determine the elbow angles that best separate (using Davies-Bouldin Index, DBI) both Non-Fatigue and Fatigue segments of the sEMG signal. Establishing the optimal elbow angle for feature extraction used in the evolutionary process wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…EMG pattern classification has attracted significant interest in current research activities due to its consolidation with the human machine controls. Noticeable research has been conducted in this area and some have reported improvements in the human machine controls such as prosthetic hand [4], [5], [6], [7]. Lots of studies have reported that the real time accuracy is generally within 90% to 97%.…”
Section: Introductionmentioning
confidence: 99%
“…EMG pattern classification has attracted significant interest in current research activities due to its consolidation with the human machine controls. Noticeable research has been conducted in this area and some have reported improvements in the human machine controls such as prosthetic hand [4], [5], [6], [7]. Lots of studies have reported that the real time accuracy is generally within 90% to 97%.…”
Section: Introductionmentioning
confidence: 99%